2018
DOI: 10.1155/2018/5438618
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Nonlinear Method for a Laterally Loaded Pile in Sloping Ground

Abstract: A simplified nonlinear method was proposed to evaluate lateral behavior of a pile located in or nearby a slope, based on the traditional p-y method. is method was validated with field test results of a steel pipe pile in clay and model tests of piles in sand slopes. e comparison indicated that the calculated horizontal displacement and bending moment of piles agree well with experimental results. en, parametric studies were performed, and it shows that horizontal displacement, rotation, bending moment, and she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…After obtaining the modified p-y curve of pile near a slope along the depth, horizontal displacement, bending moment and rotation angle along the pile can be calculated by the finite difference method using MATLAB code. Details flow chart can be found in Jiang et al [7] and Yin et al [8].…”
Section: Derivation Of the Analytical Methodmentioning
confidence: 99%
See 3 more Smart Citations
“…After obtaining the modified p-y curve of pile near a slope along the depth, horizontal displacement, bending moment and rotation angle along the pile can be calculated by the finite difference method using MATLAB code. Details flow chart can be found in Jiang et al [7] and Yin et al [8].…”
Section: Derivation Of the Analytical Methodmentioning
confidence: 99%
“…It should be noted that previous studies have not considered the influence of slope height h on the bearing capacity of piles [16,19,20,30]. When the slope height h is smaller than the maximum depth of the failure wedge development, it is clear that h will affect the ultimate resistance F su3 , as shown in equation (8). Let h be equal to 0 or let θ be equal to 0, and F su2 or F su3 will degenerate into F u for the case of pile in the ground, indicating that the theoretical derivation process of this paper is reasonable.…”
Section: Advances In Civil Engineeringmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, the lateral bearing capacity of a topconnected micropile system was studied by Kim et al [15]. Yin et al [16] proposed a new nonlinear method to evaluate lateral behaviour of a pile located in or nearby a slope, and the study clearly showed that the slope angle has a significant effect on the deflection and lateral capacity of piles. Kahribt and Abbas [17] found that, under combined vertical and cyclic lateral loads, the lateral displacement of piles decreased with an increase in the vertical load, whereas it causes large vertical displacements at all slenderness ratios.…”
Section: Introductionmentioning
confidence: 99%